Geología, Materias Primas y Áreas de Captación del Sitio con Tecnología Solutrense de la Fontanilla (Conil de la Frontera, Cádiz) - Abril, Francisco L. Torres (2012)
In this paper we review geological and lithological analysis of unpublished lithic assemblage recovered in the excavation of La Fontanilla Solutrean (Conil de la Frontera, Cádiz). The study was carried out petrological and technological remnants located in stratigraphic connection with the aim of identifying strategies selection and procurement of lithic raw materials used for the manufacture of tools.